Efektivitas Implementasi Pemberdayaan Masyarakat di Lingkungan Perguruan Tinggi dalam Mendukung Dampak Pembangunan Berkelanjutan - Ahmad Sururi; Budi Hasanah; Mayu Ma’lumatiyah; Annisa Dwianti (Universitas Sebelas Maret, 2022)
The purpose of this study is to discuss how the implementation of community empowerment supports sustainable impacts. The research method uses a qualitative approach. Data collection techniques through interviews and observation. Data analysis includes reduction, data presentation and conclusion. The results of the research show that the implementation of community empowerment policies in tertiary institutions in supporting the impact of sustainable development has not been fully effective. Achievement of the level of effectiveness was only achieved in the aspect of the degree of change in the target group and the quality of the implementation process, while in the aspect of the final result/impact of the implementation it was still not in accordance with the desired expectations. The research findings show that the concept or formulation of community empowerment policies is still very much dependent on initiation from the university so that the orientation of the community is not yet fully in the context of actual empowerment so that the outcomes or outputs impacting the implementation of empowerment policies are still not sustainable. On the other hand, even though changes in the target group and the quality of the implementation process have shown improvement, they still require efforts that are holistic in nature in encouraging an effective implementation impact.